Substitution of LRT Jabodebek Carbody Material Based on Safety Factor and Price using SPK, SAW, WP and WASPAS - Belanusa, Resi Sabanta; Asngali, Bi; Sukoroto, Sukoroto (ASTONJADRO, 2025)
This research raises the issue of substituting Jabodebek LRT carbody materials by considering safety factors and prices using three Decision Support Systems (SPK), namely Simple Additive Weighting (SAW), Weighted Product (WP), and Weighted Aggregated Sum Product Assessment (WASPAS). The results showed that it is necessary to consider the ranking of the results from the SPK against the safety factor, and price in choosing the right aluminium material for the carbody. The three GMS used gave similar rankings for aluminium materials, which shows that these methods are consistent in measuring material quality. Therefore, these three methods can be considered valid. Based on the rankings given by the three CBMS, 7034-T6 aluminium material has the highest quality, followed by 7001-T6 and 7178-T6. Lower-ranked materials include 6061-T6, 6063-T6, and 6066-T6. If budget is not an issue, it is best to choose materials with the highest quality ratings, such as 7034-T6, 7001-T6, or 7178-T6. However, if price is a priority, you should choose a material with a lower quality rating but a more economical price, such as 6061-T6, 6063-T6, or 6066-T6.